Case Report: Novel Compound Heterozygous Variants in TRIOBP Associated With Congenital Deafness in a Chinese Family - Zhou, Cong; Xiao, Yuanyuan; Xie, Hanbing; Wang, Jing; Liu, Shanling (Frontiers in Genetics, 2021)
Autosomal recessive non-syndromic deafness-28 (DFNB28) is characterized by prelingual, profound sensorineural hearing loss (HL). The disease is related to variants of the TRIOBP gene. TRIO and F-actin binding protein (TRIOBP) plays crucial roles in modulating the assembly of the actin cytoskeleton and are responsible for the proper structure and function of stereocilia in the inner ear. This study aimed to identify pathogenic variants in a patient with HL. Genomic DNA obtained from a 33-year-old woman with HL was evaluated using a disease-targeted gene panel. Using next generation sequencing and bioinformatics analysis, we identified two novel TRIOBP c.1170delC (p.S391Pfs*488) and c.3764C>G (p.S1255*) variants. Both parents of the patient were heterozygous carriers of the gene. The two variants have not been reported in general population databases or published literature. The findings of this study will broaden the spectrum of pathogenic variants in the TRIOBP gene.